Bilingual Education and Gender Difference Effect on English Achievement of Elementary School Students in Indonesia - Yassin, Muhammad; Nizarrahmadi; Muhammad Sood; Dewi Ismu Purwaningsih (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
This study attempted to investigate further issues dealing with the effect of bilingual education and gender difference on students’ English achievement especially at elementary school students. The data were collected from mid-semester test and final test of a hundred and ten students of six grade at Islamic elementary school of Al Azhar 21 Pontianak. They were divided into two big categories. Half of them belong to bilingual class, while the others were from regular class. In terms of gender, they consisted of forty-nine females and sixty four males. As the purpose of the study was to probe the effect of bilingual education and gender difference on English achievement, the results indicated that both bilingual education and gender difference do not contribute significantly on English achievements. In other words, bilinguals or females do not attain English better than monolinguals or males and vice versa. As such, the  study advocated to avoid the dichotomy of bilingual class and non-bilingual class at school, since they carried more obstacles and challenges in the classroom instruction.